Government Employees with Employment Agreements Pension Fund Valuation Across 17 Salary Grades Using Entry Age Normal and Projected Unit Credit - Khalil Rafif; Illuminata Wynnie (Indonesian Actuarial Journal, 2026)
Accurate calculation of pension funds for Government Employees with Employment Agreements (PPPK) is crucial for the sustainability of the program. Variations in the age and age of entry used can result in significantly different pension cost projections, so a comprehensive analysis is needed to determine the right methods and assumptions. This study aims to analyze the differences in the calculation of present value future benefits, normal contributions, actuarial obligations, and lumpsum benefits by taking into account based on class and age of entry. This quantitative research uses actuarial simulations using the Entry Age Normal (EAN) and Projected Unit Credit (PUC) methods. The simulation was carried out at the age of 20 to 48 years and groups I to XVII. This calculation follows the 100% one-time pension benefit for a service period of 10 to 15 years and 20% at once for a service period of more than 15 years, with a normal retirement age of 58 years. The results of the study show that the EAN method produces constant normal contributions, while the PUC method produces contributions that increase every year, the normal monthly contributions increase monotonically based on the group and age of entry into work until retirement. In addition, the EAN method produces greater lumpsum benefits than the PUC method. The 17 PPPK groups take into account the projected pension fund present value future benefits, normal contributions, actuarial liabilities, and lumpsum benefits that are more realistic and sustainable.